Caste Prejudices in Denial: Analyzing Student Perceptions in an Indian University - Anupam Yadav; Dhiraj Singha (Caste)
How do caste prejudices vary across students from different socio-economic communities? Do perceptions on caste (e.g., inter-caste marriage, existence of caste in modern times, reservation policy, etc.) correlate with caste prejudice levels? What are the factors that impact ‘Caste Prejudice Levels’ among students? In answering these questions, we measure the Caste Prejudice Levels among students of varying socio-economic backgrounds in a Central University in India. Statistical methods like two independent samples t-test, ANOVA, Chi-square test, Effect Sizes, etc., have been performed for analysing data. Overall, the results reveal that the people who are more likely to deny or are not aware of the relevance of caste today in terms of its impact on people’s lives are more likely to have higher caste prejudices. The findings provide empirical insights into the literature around caste prejudice and inform policies to eradicate caste-based discrimination, especially in higher education.